MICROPLASTICS IN AQUATIC AND TERRESTRIAL INSECTS: A GROWING ENVIRONMENTAL CONCERN - JEYASHREE J; GOPIANAND L (The Bioscan, 2024)
Microplastic pollution is an escalating global concern, infiltrating both aquatic and terrestrial ecosystems and significantly affecting insect populations. These pollutants originate from industrial waste, synthetic textiles, packaging materials, and degraded plastic products, dispersing through water, air, and soil. Their pervasive presence enables interactions with diverse insect species across multiple habitats, raising concerns about their long-term ecological consequences. Aquatic insect larvae, such as those of mayflies and chironomids, ingest microplastics directly from contaminated water or indirectly through prey, leading to severe physiological disruptions. These include developmental abnormalities, increased mortality rates, and bioaccumulation, which can transfer up the food chain. Additionally, microplastics act as carriers of toxic pollutants, such as heavy metals, persistent organic pollutants (POPs), and endocrine disruptors, exacerbating their harmful effects on insect physiology and survival. Similarly, terrestrial insects, including honeybees, fruit flies, and silkworms, encounter microplastics via atmospheric deposition and contaminated food. Ingesting these particles can cause physiological stress, gut microbiota imbalance, reduced reproductive success, and immune suppression. Wood-feeding beetles and soil-dwelling insects, such as springtails, ingest plastic fibres, disrupting nutrient cycling. Ground-dwelling species, including ants, may experience behavioural modifications due to microplastic entanglement, impairing foraging and nest-building activities. This review highlights the ingestion, bioaccumulation, and toxicity of microplastics in insects, emphasizing their ecological risks. Despite growing evidence, research gaps persist regarding their long-term consequences. Addressing these challenges requires urgent research and policies on sustainable waste management and pollution control. Mitigating microplastic pollution is crucial for preserving insect biodiversity and maintaining ecosystem functions.